Valuation of native fruits and postcolonial thinking: a search for alternatives to development (Sustainability in Debate, 2019)
This research aims to identify the influence of two paradigms, namely colonial thinking and postcolonial thinking, on the valuation of native fruits, The sample was composed of six groups of farmers from the agroecology center Luta Camponesa Nucleus, which is linked to the agroecology network Rede Ecovida de Agroecologia, and the methodological procedures were based on the principles of action research. It concludes that the colonial thinking contributes to the elimination of native fruits, as a result of epistemicide, the advancement of the green revolution, and the food empires. On the other hand, the postcolonial thinking valorizes native fruits, especially through the ecology of knowledges, agroecology, and short circuits.